The Treat of Chemical Weapons in 21st Century (Case Study: The Poisoning of Alexei Navalny with Novichok Nerve Agent) - Azizah, Yuniarti Nur; Jupriyanto; Jadhana, I.B. Putra; Ruyat, Yayat; Hafizah, Mas Ayu Elita (Jurnal Multidisiplin Madani, 2024)
Chemical weapons have been outlawed as part of CBRNE (Chemical, Biological, Radioactive, Nuclear, and Explosive) weapons under the Chemical Weapons Convention since 1993. The convention's purpose is to eradicate all types of weapons of mass destruction by preventing participating states from developing, producing, acquiring, storing, retaining, transferring, or using chemical weapons, including those developed, produced, and used. The poisoning of Alexei Navalny in 2020 with the nerve toxin Novichok sparked widespread concern about the topic of chemical weapons in the twenty-first century. This study combined qualitative methodologies with descriptive analyses to better comprehend the incident. Strict enforcement, increased international collaboration, and improved detection technology are critical to preventing their spread. This episode worsened relations between Russia and the West, highlighting the breakdown of standards prohibiting the use of chemical weapons. The same nerve toxin was used to poison Sergei Skripa and his daughter in Salisbury. This chemical is difficult to detect and has a quick and fatal effect on the human body. Its usage in attacks on humans has raised serious concerns around the world. As a result, a coordinated and comprehensive global reaction is required to confront the threat of chemical weapons while upholding international rules barring their use